2017
DOI: 10.1093/mnras/stx2395
|View full text |Cite
|
Sign up to set email alerts
|

Linear growth of streaming instability in pressure bumps

Abstract: Streaming instability is a powerful mechanism which concentrates dust grains in protoplanetary discs, eventually up to the stage where they collapse gravitationally and form planetesimals. Previous studies inferred that it should be ineffective in viscous discs, too efficient in inviscid discs, and may not operate in local pressure maxima where solids accumulate. From a linear analysis of stability, we show that streaming instability behaves differently inside local pressure maxima. Under the action of the str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 62 publications
0
34
1
Order By: Relevance
“…According to our results, the dust surface density at this position reaches ∼ 1 g cm −2 , which would imply dust-to-gas mass ratios ∼ 1 when compared with the gas surface density estimated by Fedele et al (2017). If confirmed, this inner ring would represent an ideal location to trigger the streaming instability and hence form the seeds for new young planets (Youdin & Goodman 2005;Auffinger & Laibe 2018). It is in fact possible that the streaming instability was triggered in the past at this ring, thus resulting in a run-away growth process responsible for the low values of p. Interestingly, the predicted a max at this position is not particularly high (∼ 5 mm), despite the low value of p (Abod et al 2018).…”
Section: Dust Grain Size Distributionmentioning
confidence: 93%
“…According to our results, the dust surface density at this position reaches ∼ 1 g cm −2 , which would imply dust-to-gas mass ratios ∼ 1 when compared with the gas surface density estimated by Fedele et al (2017). If confirmed, this inner ring would represent an ideal location to trigger the streaming instability and hence form the seeds for new young planets (Youdin & Goodman 2005;Auffinger & Laibe 2018). It is in fact possible that the streaming instability was triggered in the past at this ring, thus resulting in a run-away growth process responsible for the low values of p. Interestingly, the predicted a max at this position is not particularly high (∼ 5 mm), despite the low value of p (Abod et al 2018).…”
Section: Dust Grain Size Distributionmentioning
confidence: 93%
“…Self-induced dust traps are a natural way of trapping dust in rings, where the dust-to-gas ratio is larger than the classic value of 1% by one or two orders of magnitude. With such enhancements of the dust density compared to the gas, it is possible that the streaming instability and self-induced dust traps could be working together to form planetesimals in pressure bumps (Auffinger & Laibe 2018). In particular, these authors found that the streaming instability can develop in a pressure bump for discs with a higher viscosity than previously thought (α 10 −3 ) at the cost of a slower growth rate.…”
Section: Planet(esimal) Formationmentioning
confidence: 94%
“…Raettig et al (2015) showed that the accumulated pebbles could destroy a vortex in a disc, but in our case, the vortex is fed by the presence of the planet itself, which was not taken into account in their work. Auffinger & Laibe (2018) studied the linear growth regime of the streaming instability in pressure bumps in discs, and they found that streaming instability can occur within the pressure bump. The accumulated pebbles inside the pressure bump therefore turn into planetesimals, which do not affect the gas velocities and thus do not disrupt the pressure bump.…”
Section: Mass Loading In the Pressure Bumpmentioning
confidence: 99%